Sintetis Pembuatan Briket Menggunakan Limbah Buangan Pulp - Tanuwijaya, Michael; Amri, Idral; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Indonesia is one of the largest paper producing and exporting countries in the world. Along with the increase in paper production causes an increase in solid waste originating from the reject pulp. The reject pulp has the potential to produce energy because it still contains high cellulose content of around 85.16% which is able to support the provision of usable and environmentally friendly fuel. The purpose of this study was to use of reject pulp as fuel in the form of briquettes by mixing coconut shell charcoal as cofiring and CPO sludge as an adhesive. Briquettes will mixed with a variety of composition of reject pulp and coconut shell charcoal cofiring from 80%: 0%, 20%: 60%, 30%: 50%, 50%: 30%, 60%: 20%, and 0%: 80% , for adhesive 20% while 90%: 0%, 30%: 60%, 40%: 50%, 50%: 40%, 60%: 30%, 70%: 20% and 90%: 0% for adhesive 10 % of the total briquette weight which is ± 2 grams. The briquettes that have been form must qualified to the quality standards of SNI for wood charcoal (No.1 / 6235/2000) where after being tested only a few compositions have qualified the standards, for the reject pulp composition and coconut shell charcoal cofiring from 0:90, 30:60 40:50 with an adhesive composition of 10% and a composition of 0:80, 20:60, 30:50 with an adhesive composition of 20%, with the highest calorific value of 5274 cal/g and ash content of 2.65%. Key words: Briquettes, Coconut shell charcoal, CPO sludge, Reject pulp,